2023
DOI: 10.1186/s40462-023-00390-5
|View full text |Cite
|
Sign up to set email alerts
|

Context drives movement patterns in a mobile marine predator

Abstract: Intra-specific variability in movement behaviour occurs in all major taxonomic groups. Despite its common occurrence and ecological consequences, individual variability is often overlooked. As a result, there is a persistent gap in knowledge about drivers of intra-specific variability in movement and its role in fulfilling life history requirements. We apply a context-focused approach to bull sharks (Carcharhinus leucas), a highly mobile marine predator, incorporating intra-specific variability to understand h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…As a top predator it is hard to argument that the primary productivity could determine the occurrence patterns directly. However, some fish species like the yellowtail amberjack, Seriola lalandi , that are bull shark prey, tend to aggregate and spawn when the chlorophyll is high ( Sala et al, 2003 ; Lubitz et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a top predator it is hard to argument that the primary productivity could determine the occurrence patterns directly. However, some fish species like the yellowtail amberjack, Seriola lalandi , that are bull shark prey, tend to aggregate and spawn when the chlorophyll is high ( Sala et al, 2003 ; Lubitz et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals were also recorded revisiting coastal areas on multiple years post-release. Many animals, across a variety of taxa exhibit philopatry [ 68 ], with individuals repeatedly returning to the same stretch of coast for reproductive needs [ 66 , 69 , 70 ], foraging opportunities [ 37 , 71 , 72 , 73 ] or for reasons still largely unknown [ 26 ]. Additionally, ocean currents [ 19 ], water temperature [ 18 , 74 , 75 , 76 , 77 ], rainfall [ 38 , 39 ] and swell height [ 26 , 78 ] are well documented drivers of shark movement patterns and drivers of the behaviour shown here.…”
Section: Discussionmentioning
confidence: 99%
“…acoustic receivers) attributes as explanatory variables Robins, Snijders, et al, 2007;Snijders et al, 2006). These models account for the non-independence of the data expressed as movements between sites acting as sources or sinks (Silk & Fisher, 2017) Bull shark movements are known to be influenced by both biotic and abiotic factors (Lee et al, 2019;Lubitz et al, 2023;Niella et al, 2022;Werry et al, 2018), and anthropogenic factors (Hammerschlag et al, 2022;Werry et al, 2012), but less is known about the importance of con-and heterospecifics in movement decisions. Even if most studies on the movements of these marine predators have identified environmental factors as most influential to their movement ecology, we expect that social and competition factors may be just as important in explaining individual movements.…”
mentioning
confidence: 99%